Advanced Planning in Fresh Food Industries Integrating Shelf Life into Production Planning - Lütke Entrup, Matthias (Contributions to Management Science, 2005)
Production planning in fresh food industries is a challenging task. Although modern Advanced Planning and Scheduling (APS) systems could provide significant support, APS implementation numbers in these industries remain low. Therefore, based on an in-depth analysis of three sample fresh food industries (dairy, fresh and processed meat), the author evaluates what APS systems should offer in order to effectively support production planning and how the leading systems currently handle the most distinguishing characteristic of fresh food industries, the short product shelf life. Starting from the identified weaknesses, customized software solutions for each of the sample industries are proposed that allow to optimize the production of fresh foods with respect to shelf life. The book thereby offers valuable insights not only to researchers but also to software providers of APS systems and professionals from fresh food industries.